Modeling the Demand for Islamic Microfinance Services: An Application of PLS-SEM Approach - Mohamed Asmy Bin Mohd Thas Thaker; Salina Kassim; Md Fouad Bin Amin; Marhanum Che Mohd Salleh; Nadhrah Othman; Siti Nadhirah Kassim (Universitas Muhammadiyah Yogyakarta, 2022)
The access to capital is very crucial for ensuring the financial sustainability of microfinance clients. It is also equally important to determine the demand for microfinance services among the clients. This study aims to identify the factors affecting the demand for Islamic microfinance (IsMF) services among the women micro-entrepreneurs in Malaysia. This study has collected a total of 250 samples from the field survey on women micro-entrepreneurs who are also the clients of Amanah Ikhtiar Malaysia (AIM). In addition, Partial Least Squares (PLS) method used to identify the potential factors (4As) i.e., affordability, accessibility, adequacy and awareness affecting the demand for IsMF. The results show that only “accessibility” has significant and positive relation with the demand for IsMF. Besides, the measurements items of accessibility such as distance of IsMF institution, collateral requirement, guarantor requirement, application procedure and process, repayment method, service efficiency, advise and consultation, and number of IsMF centers are the key factors affecting the demand for IsMF services in Malaysia. This paper provides some insights for the policy makers of Islamic microfinance and recommends that IsMF providers should take accessibility factor into greater consideration for the economic upliftment of women in microenterprises in Malaysia